THE MASK, MASKING AND CURTAILMENT OF DOMESTIC TERRORISM IN IKA THROUGH AKAKUM PERFORMANCE OF NTO USOH PEOPLE IN AKWA IBOM STATE - Akpan, Margaret; Udofia, Anietie Francis (International Review of Humanities Studies, 2019)
n today`s Nigeria, unchecked spate of violence has gradually surfaced through slippages in human character and garner to domestic terrorism in many communities. Consequences reflect in development plans schemed for these communities. Ika community has experienced this setback significantly among others in terms of development. The dimensions the institutions responsible for countering this enigma take seem to aggravate more terrifying scenarios which end in injuries, tears and even loss of lives. This paper examines how the costumes of Akakum performance tone down domestic terrorism in Ika community. It uses qualitative methodology and interview as its methodology and bases the framework on functionalism. Findings show that chaos are developing in communities as sub-cultures like traditional performances which were viable tools for curtailing antisocial manners have been relegated to the background because of the constant absorption of foreign cultures that do not fit into the context of Nigeria’s perception of social manners. Traditional performances maintain in-built principles that prevent members from transgressing. The body accessories of Akakum are believed to embody supra-mundane powers which deter initiates from indulging in domestic terrorism that pervaded Ika community for many years. The paper concludes that traditional performances should be revitalized, secularized and given a global appeal. If traditional performances are secularized, they may attract tourists` interest; become a foreign income earner and also serve as tools of social control and development in the community